Extension Agent Attitudes Toward Paired/Cooperative Computer·Assisted Instruction for In· Service Training - Joseph R. Makuch; Paul D. Robillard (Journal of Applied Communications, 1994)
Successful integration of CAI (computer-assisted instruction) into Cooperative Extension in-service training programs requires acceptance of CAI by staff